Pelaksanaan Pengadaan Tanah Dan Pemberian Ganti Rugi Dalam Rangka Pembangunan Jalan Tol Pejagan-Pemalang Wilayah Kabupaten Tegal (Studi Kasus Putusan No.36/Pdt.G/2015/PN.Slw) - Ramadhani, Nurina; , Shalman Al-Farizi, S.H.,M.Kn (2017)
This research aimed to analyze the dispute of the implementation of land procurement for public interest, in this case, the compensation allotment in Pejagan-Pemalang Highway Construction at Tegal Regency especially on case number 36/Pdt.G/2015/PN.Slw and its adjudication, so that it has legal force. The result of this research showed that, based on article 31 of the consitution number 2 of 2012 about Land Procurement for Construction for Public Interest, the appraisal of land procurement object for public interest compensation was done by Evaluator whom appointed by the Head of Procurement Implementer and it went through discussion process which was done to determine the restitution that would be given to the owner of the land whom became the land procurement object, it was not bargaining about the value of the compensation. The land dispute related to right extrication for public interest could be solved by mediation without court process.